2016
DOI: 10.1038/ncomms11625
|View full text |Cite
|
Sign up to set email alerts
|

Alanine aminotransferase controls seed dormancy in barley

Abstract: Dormancy allows wild barley grains to survive dry summers in the Near East. After domestication, barley was selected for shorter dormancy periods. Here we isolate the major seed dormancy gene qsd1 from wild barley, which encodes an alanine aminotransferase (AlaAT). The seed dormancy gene is expressed specifically in the embryo. The AlaAT isoenzymes encoded by the long and short dormancy alleles differ in a single amino acid residue. The reduced dormancy allele Qsd1 evolved from barleys that were first domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
125
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 46 publications
6
125
0
Order By: Relevance
“…3). These results are in agreement with the expression profiles and organ specificity of Qsd1 in barley, as well as the rice Qsd1 ortholog [9]. The results also support the homeology of barley and wheat Qsd1 sequences observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…3). These results are in agreement with the expression profiles and organ specificity of Qsd1 in barley, as well as the rice Qsd1 ortholog [9]. The results also support the homeology of barley and wheat Qsd1 sequences observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier, it has been successfully demonstrated by Sato et al . () that the previously reported candidate genes can be validated the previously reported candidate gene, followed by its use in improving target trait. Therefore, we advanced the same population in this study for applying QTL‐seq approach to perform high‐resolution trait mapping and identify genomic region(s) associated with FSD.…”
Section: Discussionmentioning
confidence: 97%
“…The DArT and DArTseq are useful genotyping approaches but they do not provide exact position of SNPs in the reference genome which is very much required for performing fine mapping, candidate gene discovery and marker development. Earlier, it has been successfully demonstrated by Sato et al (2016) that the previously reported candidate genes can be validated the previously reported candidate gene, followed by its use in improving target trait. Therefore, we advanced the same population in this study for applying QTL-seq approach to perform high-resolution trait mapping and identify genomic region(s) associated with FSD.…”
Section: Discussionmentioning
confidence: 98%
“…A specific role for Ala ATs had been related to seed dormancy (Sato et al . ) and to specific stress responses, especially oxygen deprivation and nitrogen limitation (Shrawat et al . ; Rocha et al .…”
Section: Introductionmentioning
confidence: 99%